Development of Digital Teaching Materials Based on Material: Revolution on the Edge of Jakarta 1945-1955 for Grade XI IPS at SMAN 4 Cibinong - Nurhidayati, Annida Fitri; Widodo, Tubagus Umar Syarif Hadi; Fauzan, Rikza (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This study aims to develop local history-based digital teaching materials for the XI IPS class history subject at SMAN 4 Cibinong. This study uses an R&D research approach using the ADDIE development model. Based on the results of the needs analysis, history learning has not developed teaching materials based on local history because learning local history has not been optimal. This research focuses on the proclamation of 17 August 1945 and the social revolution on the outskirts of Jakarta 1945-1955. The design of digital teaching materials is designed in the form of an e-book using the Canva application and professional pdf flipbook. Based on the results of the due diligence validation questionnaire, it obtained very feasible criteria with a percentage of material expert validation 90%, linguist validation 90%, media validation 98%, and practitioner validation 82.5%. After the expert and practitioner validation tests were declared feasible, the research continued with the implementation of limited trials. Trial in class XI IPS 1 with a total of 34 students. Based on the results of the practice of student responses, they obtained an assessment of the percentage of 85.39% with very practical criteria. Based on the trial results, digital teaching materials for the Social Revolution on the outskirts of Jakarta 1945-1955 are suitable for use in history lessons for class XI IPS at SMAN 4 Cibinong.